Modeling Favipiravir Antiviral Efficacy Against Emerging Viruses: From Animal Studies to Clinical Trials. (28th April 2020) - Madelain, Vincent; Mentré, France; Baize, Sylvain; Anglaret, Xavier; Laouénan, Cédric; Oestereich, Lisa; Nguyen, Thi Huyen Tram; Malvy, Denis; Piorkowski, Géraldine; Graw, Frederik; Günther, Stephan; Raoul, Hervé; et al.
Abstract : In 2014, our research network was involved in the evaluation of favipiravir, an anti‐influenza polymerase inhibitor, against Ebola virus. In this review, we discuss how mathematical modeling was used, first to propose a relevant dosing regimen in humans, and then to optimize its antiviral efficacy in a nonhuman primate (NHP) model. The data collected in NHPs were finally used to develop a model of Ebola pathogenesis integrating the interactions among the virus, the innate and adaptive immune response, and the action of favipiravir. We conclude the review of this work by discussing how these results are of relevance for future human studies in the context of Ebola virus, but also for other emerging viral diseases for which no therapeutics are available.